Kajian Teologis Tentang Judi Online Slot Terhadap Keimanan Orang Kristen Masa Kini - Rusmiyanto, Andreas Danang (APOSTOLOS, 2024)
The desire to obtain abundant wealth is everyone's dream. Especially if the way to get it is easy. In essence, gambling is an act that is contrary to religious, moral, decency and legal norms, and is dangerous to the livelihood and life of the community, nation and state. Gambling can also cause losses to those who do it, even though it sometimes provides benefits. But the profits obtained from gambling cannot be used as a justification. In this article the author uses a qualitative descriptive method by reviewing literature from various sources, data and scientific journals related to the subject of discussion about online slot gambling. The author hopes that through this theological study he can provide an explanation of how Christians behave in facing today's challenges, especially online slot gambling.